Differentiation of Yersinia enterocolitica enteritis from other bacterial enteritides by ultrasonography: A single-center case-control study - Eri Miyata; Keisuke Jimbo; Reiko Kyodo; Mitsuyoshi Suzuki; Takahiro Kudo; Toshiaki Shimizu (Elsevier, 2022)
Background: The diagnosis of Yersinia enterocolitica (Ye) enteritis is not easy because detection from stool culture is more difficult for Ye than for other bacterial enteritides. The establishment of characteristic ultrasonographic findings for Ye enteritis would help improve the detection rate of Ye enteritis along with performance of several cold cultures. This would facilitate appropriate selection of antibiotics based on antimicrobial susceptibility testing and contribute to a more accurate understanding of local public health. This study aimed to retrospectively compare ultrasonographic findings and clinical features between children with Ye enteritis and other bacterial enteritides. Methods: We identified patients treated for Ye enteritis (Ye group; n = 27) or other bacterial enteritides (Other enteritis group; n = 29) between 2014 and 2018. Ultrasonographic findings (including mean maximum diameter and mean major-minor axis ratio of ileocecal lymph nodes, wall thickness of the terminal ileum, and presence of a pericecal hyperechoic region), clinical symptoms, and laboratory findings at first visit were compared between groups. Results: No difference in mean maximum diameter of ileocecal lymph nodes was seen between groups. However, mean major-minor axis ratio of ileocecal lymph nodes was lower in the Ye group than in the Other enteritis group (p < 0.001). Presence of a pericecal hyperechoic region was more frequent in the Ye group than in the Other enteritis group (p < 0.001). The combined presence of a mean ileocecal lymph node major-minor axis ratio <1.51 and a pericecal hyperechoic region offered 100% sensitivity. Conclusion: Characteristic ultrasonographic findings identified in this study may improve ultrasonographic differentiation of Y. enterocolitica enteritis from other bacterial enteritides.